Peran Pondok Pesantren dalam Membentuk Karakter Anak Muda di Era Modern - Alisia Zahro’atul Baroroh; Abdul Khobir (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
The rapid development of technology and increasingly complex global challenges have a significant impact on the mindset and behavior of today's youth. Pondok pesantren, as a traditional Islamic educational institution, plays a crucial role in shaping the character of young people, fostering good morals, discipline, and responsibility. This study aims to explore the role of pondok pesantren in character building among youth in the modern era. The research adopts a qualitative approach, using data collection techniques such as in-depth interviews, observations, and document analysis with pesantren leaders, teachers, and students. The findings indicate that pondok pesantren play a vital role in shaping students' character through religious education, the application of daily routines that instill discipline, and social activities that promote a sense of responsibility. Pondok pesantren also adapt to modern times by incorporating technology into the learning process while maintaining traditional values. In conclusion, pondok pesantren are effective in shaping a generation of youth who are not only intellectually capable but also possess strong character, discipline, and high moral standards.